14.2k views
5 votes
I need help with this question plsss

I need help with this question plsss-example-1
User TimP
by
5.2k points

1 Answer

6 votes

Answer:

In standard form, the answer is
(f*g)(x)=x^(6)+6x^(4)+8x^(2)+2.

Explanation:


(f*g)(x) is the same as saying
f(g(x)).

Simply put, sub into
f(x) using the definition of
g(x) as an x-value.


f(x)=x^(3)-4x+2\\g(x)=x^(2)+2\\\\(f*g)(x)=f(g(x))\\\\(f*g)(x)=(x^(2)+2)^(3)-4(x^(2)+2)+2\\(f*g)(x)=[ (x^(2)+2)(x^(2)+2)(x^(2)+2) ] -4x^(2)-8+2\\(f*g)(x)=[ (x^(4)+4x^(2)+4)(x^(2)+2)]-4x^(2)-6\\(f*g)(x)=x^(6)+6x^(4)+12x^(2)+8-4x^(2)-6\\(f*g)(x)=x^(6)+6x^(4)+12x^(2)-4x^(2)+8-6\\(f*g)(x)=x^(6)+6x^(4)+8x^(2)+2

User JamesWatling
by
5.9k points